Music Performance and the Second Person - Martínez, Isabel Cecilia (2021)
Research on the psychology of music performance acknowledges a long tradition. During the last forty years, knowledge was built around the ways in which performers develop sophisticated mechanisms to regulate time and dynamics, and to temporarily align their own performance, entraining with the music they play and with the music performed by others. More recently, attention has been paid to the bodily cues that allow communication among the performers. However, in spite of music being a social practice, little is known about the role of social cognition in music performance. In particular, (i) how musicians communicate between each other through music, (ii) how they understand each other’s feelings, and (iii) how they interpret the mental states of their partners. The Second Person Perspective of mental attribution is a postcognitivist theory that grew in the intersection between philosophy and psychology, focusing on the ways human beings interact and understand each other’s minds. Its central thesis is that in face-to-face/body-to-body interactions, the individuals make direct and reciprocal attributions about the other’s mental states, that ground the development of other general cognition -including social cognition- abilities. For the first time four stylistic music performance practices are investigated under this framework.